PENELITIAN KUALITAS AIR PADA MATA AIR YANG ADA DI DALAM DAN DI LUAR TUBUH BENDUNGAN JATILUHUR PURWAKARTA-JAWA BARAT - Santosa, Rahmadi Herman (JURNAL SUMBER DAYA AIR, 2018)
An Acencer water spring with a discharge of 2 – 4 L/sec. was observed at the underground correlation tunnel of the hydro-electric generator room of the Jatiluhur Dam. Unfortunately this spring was never utilized. Whereas actual condition of this spring water is of such good quality that Dr. Basuki Hadimulyono, former Director General of the R&D Agency for Ministry of Public Works had assigned the head of the Experimental Station for Water Resources Environment, Research Center of Water Resources, to conduct a research on the possible water use. Based on in-situ research, a water spring was not only found inside the dam body but also outside. This water spring generates a discharge of 3 – 5 L/sec. Results of the research concluded that with indicated water discharge, both sources can be utilized continuously without disturbing other parts of the dam body. However, water quality has to be treated in order to meet the drinking water criteria particularly regarding the excessive content of Manganese and E-Coli